2011
DOI: 10.1038/cdd.2011.124
|View full text |Cite
|
Sign up to set email alerts
|

Isoform-specific palmitoylation of JNK regulates axonal development

Abstract: The c-jun N-terminal kinase (JNK) proteins are encoded by three genes (Jnk1-3), giving rise to 10 isoforms in the mammalian brain. The differential roles of JNK isoforms in neuronal cell death and development have been noticed in several pathological and physiological contexts. However, the mechanisms underlying the regulation of different JNK isoforms to fulfill their specific roles are poorly understood. Here, we report an isoform-specific regulation of JNK3 by palmitoylation, a posttranslational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 40 publications
(90 reference statements)
1
44
0
Order By: Relevance
“…The importance of palmitoylation in DLK-JNK signaling is reinforced by a report that another member of this pathway, the neurally-enriched JNK3, is also palmitoylated (Yang et al, 2012). In peripheral neurons JNK3 plays key roles in retrograde responses to axonal injury and was previously reported to colocalize with JIP3 on axonal vesicles (Keramaris et al, 2005, Cavalli et al, 2005).…”
Section: Additional Roles For Palmitoylation In Dlk-jnk Pathway Signamentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of palmitoylation in DLK-JNK signaling is reinforced by a report that another member of this pathway, the neurally-enriched JNK3, is also palmitoylated (Yang et al, 2012). In peripheral neurons JNK3 plays key roles in retrograde responses to axonal injury and was previously reported to colocalize with JIP3 on axonal vesicles (Keramaris et al, 2005, Cavalli et al, 2005).…”
Section: Additional Roles For Palmitoylation In Dlk-jnk Pathway Signamentioning
confidence: 99%
“…These studies reported an impressive number of palmitoyl-proteins, but did not identify several palmitoylated neuronal proteins, including kinases, that have been identified in targeted studies e.g. (Yang et al, 2012, Holland et al, 2016, George et al, 2015, Levy et al, 2011). This raises the strong possibility that additional studies from different neuronal preparations may identify additional palmitoyl-kinases.…”
Section: How Many Palmitoyl-kinases Are There?mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the long (p54) isoforms of JNK1 and JNK2 harbor a caspase cleavage site and their C termini can be processed during the onset of apoptosis, with unclear functional consequences (171). Lastly, the N-and Cterminal-lengthened JNK3␣2(L) isoform of JNK3 was palmitoylated on its C terminus by the DHHC family palmitoyltransferase ZDHHC15, which regulates JNK3␣2(L) subcellular localization and activity; in contrast, the almost-identical C terminus of JNK1␣2 was not palmitoylated (172). Taken together, these studies reinforce the differences in the potential regulatory mechanisms for the different JNK isoforms.…”
Section: Activities and Modifications Of Individual Jnk Isoformsmentioning
confidence: 99%
“…First, JNK3 in neurons undergoes isoform-specific palmitoylation, a lipid modification that generally enhances the hydrophobicity of proteins and regulates their association with membrane structures. Palmitoylation of JNK3 impedes axon growth, a process that relies on active Golgi functions 4 . Second, palmitoylation directs JNK3 to the Golgi complex.…”
mentioning
confidence: 99%